Operational characteristics of rotor/stator mixers - Sparks, T. (Cranfield University, 1993)
Fast chemical reactors require rapid mixing, and literature shows that rotor/stator mixers can provide this. Results have been published, at small scale, showing rotor/stator mixers to be promising as chemical reactors. An industrial size rotor/stator mixer has been procured and fitted into a test loop. Instrumentation was used to measure shaft torque, shaft speed, differential pressure and differential temperature. Measurements were used to produce an energy balance for the mixer that could be used to assess its mixing performance, based upon general descriptions of mixing. Residence time distribution (RTD) curves were obtained and it was shown that the mixer exhibited substantial backmixing. Modifications to the mixer are proposed that may produce a RTD that better approximates plug flow. It is concluded that if the mixer could be made to better approach plug flow, as mixing rates would be very high, use of such a device could improve the product quality from a competitive chemical reaction.